The Internal and External Determinants of Cost Efficiency in the U.S. Commercial Banks - Li, Ruohan (2019)
This paper employs two models to provide empirical evidence on the impact of internal and external determinants on cost efficiency in the U.S. The sample consists of 76 commercial banks in the U.S. with 547 observations. Stochastic Frontier Analysis (SFA) model is used for the first step. Four pre-tests are conducted to test the applicability of data and the model. After passing Gamma, M3T, skewness, and likelihood ratio test, cost efficiency scores can be worked out by SFA. In the second step, the scores are regarded as the dependent variables in the Tobit regression model. Bank-level variables such as the logarithm of total assets, loan loss reserves to gross loans, equity to assets, and return on average return, as well as country-level like GDP, inflation, and unemployment rate, are treated as independent variables. Correlation and coefficients are identified in the Tobit regression model. The results indicate that too big to fail issues exist in the estimation of cost efficiency. Large banks tend to be less cost-efficient than those small counterparts because banks with large assets lean on the bailout of government. Besides, more cost inefficiency is contributed by medium-sized banks. Loan loss reserves to gross ratio has a negative relationship with cost efficiency. Banks with high-quality assets normally decrease the amount of loan loss reserves during a good economic condition. As a result, the decline of reserves for loss losses enhances cost efficiency. Regulations about capital impede the cost efficiency. Profitability can be reflected by the return on average assets ratio. Banks with high profitability have less cost efficiency. Those banks can promote their cost efficiency by improving cost control ability and downsizing staff. There is a negative impact of unemployment rate on cost efficiency however no significant relationship is founded among GDP growth rate, inflation and cost efficiency.